Profile of clinical research related to orthopedic disorders in the last five years - Lopez Martinez, Luis; de Oliveira Candido, Caio; da Silva Naresse, Vinicius; Carraro Lolo, Bruno; Lima dos Santos, Silvonete; Leme Godoy-Santos, Alexandre (Journal of the Foot & Ankle, 2022)
Objective: The aim of the study was to identify the profile of clinical research related to orthopedic disorders worldwide. Methods: A survey of clinical research in orthopedics was performed in the ClinicalTrials.gov platform and Plataforma Brasil databases. Results: According to data from the ClinicalTrials.gov platform, 1.142 clinical trials related to orthopedic disorders were registered from January 2017 to July 2022. Brazil is in the 14th position in the international ranking, and the Universidade de Sao Paulo (USP) occupies the 6th position among the collaborators who performed the most research in this area. The importance of the foot and ankle area in clinical research related to orthopedic disorders is evident when it is the 7th most studied worldwide and the 2nd most studied in Brazil. Most clinical trials related to orthopedic disorders worldwide target the adult or older adult population and involve interventional studies. On the other hand, most of the clinical trials related to orthopedic disorders in Brazil target the pediatric or geriatric population and involve observational studies. Conclusion: The profile of clinical research related to orthopedic disorders worldwide showed that most clinical trials targeted the adult or older adult population and aimed to treat patients, not prevent diseases. Brazil targeted the pediatric or geriatric population focusing on characterizing populations and diseases. Clinical research related to orthopedic disorders performed worldwide and in Brazil depended on sponsorship and private institutions. Level of Evidence IV; Descriptive Observational Study.